MANFAAT LEGALITAS P-IRT BAGI PENGEMBANAGN USAHA DALAM PROGRAM IbM KRIPIK PISANG BERKULIT - Naimah, Naimah; Soesilo, Soesilo (Universitas Muhammadiyah Jember, 2015)
Problems faced [by] banana kripik have husk [to] property of UD.SHABRINA can be grouped in three Aspect that is: ( 1) Legality Product there is no ( 2) product promotion, ( 3) Problem of Produksi.Dari three most aspect [of] urgen [is] legality, therefore this solution will focussed [at] problem of legality benefit and procedures of kripik banana have husk [to] of UD.SHABRINA [in] on duty Health Of Sub-Province of Lumajang. Method the used [is] training relate to product security and legality of P-Irt and adjacent in course of registration of P-Irt product of kripik banana of bernkulit. Reached result in legality aspect in the form of: Result of Test Laboratory, certificate of P-Irt. And benefit as a means of protection of law and also facilitate marketing obtained benefit there [is] Change after pelaksaan of program of Ibm UD. Shabrina more self confidence market its product, besides supported with Appliances [gift/ giving] of Ibm in the form of a set slice appliance and knife have eye [to] four. functioning precisely utilize to support the make-up of result of earnings and production 35%.